Digital Tools for Accounting and Analytical Support of Enterprises: Innovation and Management Aspect - Prodanchuk, Mykhailo; Dankevych, Andrii; Aksonova, Oksana; Tomchuk, Olena (Dr. Viktor Koval, 2023)
Introduction. The modern global economy requires the digitalization of all spheres of enterprise activity, including accounting and analytical processes. This creates new synergistic effects on all related production, management, and business processes and new opportunities and business directions. The analytical process begins to include new information resources, which gives an impetus to the systematic development of support for decision-making by the management of enterprises, increasing the level of relevance of management decisions, and providing opportunities for operational restructuring of market tactics and strategies. Aim and tasks. The study aims to introduce digital tools for analytical accounting support for Ukrainian enterprises based on innovative management aspects and develop a mathematical model for using digital resources to optimize the architecture of enterprise information systems. Results. A mathematical model of the use of digital resources was developed to optimize the architecture of the company's information systems. The process of introducing digital tools for accounting and analytical support of enterprises in Ukraine was also studied and compared with the practice of their implementation under the conditions of “Economy 4.0” in developed countries. The advantages of introducing digital tools for accounting and analytical support were determined and obstacles to this process are named. It is indicated that the main guarantee of the effectiveness of the use of digital tools in view of the innovation-management aspect of their implementation is adaptability to internal and external influences, technological innovations, changes in tasks, goals, and even the sphere of economic activity of the enterprise. It is noted that this largely depends on the architecture of the information systems. According to estimates, the annual “cumulative effect” growth rate from introducing IT technologies in accounting and analytical processes may exceed 19%. Conclusions. The developed mathematical model makes it possible to propose a new approach to the transformation of the system of digital accounting tools and analytical support instead of the traditional eclectic approach, which ensures effective auxiliary functionality or implements new functionality of the entire information management system, the elements of which are digital accounting tools. Factors that prevent the implementation of digital tools, which will increase the competitiveness of Ukrainian enterprises, are indicated.